A convenient separation method for di(2-ethylhexyl)phthalate by novel superparamagnetic molecularly imprinted polymers. Issue 63 (25th October 2018) - Yuan, Xinhua; Liu, Tiantian; Gao, Lei; Xing, Lu; Zhu, Yingying; Li, Songjun
Abstract : Through surface molecular imprinting technique and coating superparamagnetic Fe3 O4 nanoparticles with molecularly imprinted polymers, a novel MMIP was successfully fabricated for the convenient separation of DEHP. Abstract : Through a surface molecular imprinting technique and coating superparamagnetic Fe3 O4 nanoparticles with molecularly imprinted polymers (MIPs), a novel magnetic molecularly imprinted polymer (MMIP) was successfully fabricated for the convenient separation of di(2-ethylhexyl)phthalate (DEHP) with methacrylic acid as functional monomer, ethylene glycol dimethacrylate as cross linker and 2, 2-azobis(isobutyronitrile) as initiator. A magnetic non-molecularly imprinted polymer (MNIP) was also prepared for comparison purposes. The morphology structure and the magnetic properties of MMIP were characterized by transmission electron microscopy (TEM), Fourier transform infrared spectrometry (FT-IR), X-ray diffraction, vibrating sample magnetometry (VSM) and thermo gravimetric analysis (TGA). The adsorption properties of MMIP and MNIP were investigated by static and dynamic adsorption experiments. The results show that the diameter of the synthesized MMIP microspheres is about 300–500 nm with good dispersibility in solvent. The prepared MMIP shows superparamagnetic properties with the maximum saturation magnetic intensity of 43.97 emu g −1, and it can be conveniently separated using an external magnetic field. Compared with MNIP, MMIP has a higher adsorption capacity and better adsorption selectivity for DEHP, and the imprinting factor reaches 3.012. The regeneration adsorption experiment illuminates that the novel MMIP can be reused with good separation efficiency.